Organizational Communication Strategy For Quick Public Response Service In Cilandak Sub-District, South Jakarta In Improving The Image - Saktisyahputra; Sutanto, Agung (Yayasan Sinergi Kawula Muda, 2023)
This study was conducted to analyze the organizational communication strategy for the Quick Public Response (CRM) service in Cilandak Sub-District in improving the image. A communication strategy is an organizational plan to manage the strategy of the newly developed ideas, combined with the recipient of the message through the media, and achieve the effect of good communication goals. The data analysis technique used was descriptive qualitative analysis through observation and interviews. The sources of data were primary and secondary data. The field research data collection method was in the form of observation, interviews, and literature study. The interview technique was carried out in a structured manner. The resource persons in this study were 6 people, i.e., the Head of Cilandak Sub-district, Head of the Government Section of the Cilandak Sub-District Office, Communication Lecturer at the Stiami Institute of Social Sciences and Management, Service Staff of the Cilandak Sub-District Office, and the people of Cilandak Sub-District. From the results of this analysis, the organizational communication strategy of the CRM service in Cilandak District in improving the image has implemented research indicators in accordance with the objectives of the CRM service.